WOMEN'S LEADERSHIP IN THE FIQH OF ABDUL QODIR:: Reciprocal Reading Tafsir Hadits - Farhanah, Ghina; F., Fatihunnada; Hidayatulloh, Muhammad (Sekolah Tinggi Ilmu Al-Quran dan Sains Al-Ishlah, 2024)
The Prophet’s Hadith is considered the second source of legislation in Islam after the Holy Qur’an, and it can be interpreted in a textual and contextual manner. Some hadiths need interpretations from the texts of the Holy Qur’an to understand the studied hadith. This research focuses on the hadith on women’s leadership, which is studied using the reciprocal reading method invented by the religious jurist Abdul Qadir. The meaning of the reciprocal reading is to create an equal relationship between men and women in Islamic texts, because reality shows that the interpretation of Islamic texts partly tends towards male dominance and the marginalization of women, especially in the issue of leadership. Therefore, this research aims to know the leadership of women in the hadith “All of you are shepherds and each of you is responsible for his flock” from the perspective of the “reciprocal reading” according to the religious jurist Abdul Qadir. One of the results of this research is that female leadership from the perspective of reciprocal reading is a leadership model that does not make it difficult for women to stand before men, whether in the private or public sphere. As for the concept of actual implementation in this approach, it is: First, the way of looking (view) in which humanity is respected. The way to read reference texts is to position men and women as subjects and as complete human beings. The method of classification, or in the Arabic term (rule), is experience, exchange, or cooperation between men and women.